2019
DOI: 10.1136/archdischild-2018-315962
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating diagnosis for childhood brain tumours: an analysis of the HeadSmart UK population data

Abstract: BackgroundHeadSmart, a public and professional awareness campaign, was launched to enhance awareness of brain tumour symptomatology identified in the Royal College of Paediatrics and Child Health, National Institute for Health and Care Excellence–accredited guideline. Quality improvement data showed a reduction in diagnostic interval nationally. To reach the government target of 4 weeks, we need to identify subgroups with ongoing delays.MethodsIncident cases of brain tumours (0–18) diagnosed between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 13 publications
6
30
1
Order By: Relevance
“…They included patients with eye movement disorders, such as diplopia or strabismus, as A recent report from "Head Smart" shows that the tumor subtypes with the longest DI ("system interval" in their paper) were craniopharyngioma (median 3.3 weeks) and optic pathway glioma (median 3.3 weeks), which often present with visual difficulties. 19 Though this trend corresponds to our results, the median DI of 8 patients…”
Section: Neuro-oncology Practicesupporting
confidence: 90%
See 1 more Smart Citation
“…They included patients with eye movement disorders, such as diplopia or strabismus, as A recent report from "Head Smart" shows that the tumor subtypes with the longest DI ("system interval" in their paper) were craniopharyngioma (median 3.3 weeks) and optic pathway glioma (median 3.3 weeks), which often present with visual difficulties. 19 Though this trend corresponds to our results, the median DI of 8 patients…”
Section: Neuro-oncology Practicesupporting
confidence: 90%
“…The median age at diagnosis in our study was similar to those in Brain Tumor Registry of Japan 18 and similar studies in Japan 12 and other Western countries. 6,11,17,19,20 The proportion of tumor types and locations were similar to the Brain Tumor Registry of Japan, including the higher frequency of germ cell tumor.…”
Section: Neuro-oncology Practicementioning
confidence: 55%
“…We also found that the fall in incident diagnoses was specific to certain tumour types, including CNS tumours and lymphomas. These tumour types, particularly TYA lymphomas, are known to have protracted patient intervals and subsequent delays in presentation 21 30. Pandemic-related changes in health-seeking behaviour could provide an explanation to our findings.…”
Section: Discussionmentioning
confidence: 57%
“…The HeadSmart public and professional awareness campaign was launched in 2011 in the UK, aiming to raise awareness of the signs and symptoms of brain tumours in children due to the long DIs. The campaign has been associated with a reduction in the TDI from 14.4 weeks in in 2006 to 6.5 weeks in 2015 17 18…”
Section: Discussionmentioning
confidence: 99%